2004
DOI: 10.3748/wjg.v10.i8.1141
|View full text |Cite
|
Sign up to set email alerts
|

Significant correlation between expression level of HSP gp96 and progression of hepatitis B virus induced diseases

Abstract: AIM: Gp96, also known as Grp94, is a member of heat shock protein (HSP) family and binds repertoires of peptides thereof eliciting peptide-specific T cell immune responses. It predominantly locates inside the endoplasmic reticulum (ER) with some cell surface expression in certain cancerous cells. Previous studies have shown that gp96 expression level was up-regulated in tumor cells, including hepatocellular carcinoma (HCC). However, relationship between the extent of gp96 expression and disease progression esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
15
1
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 42 publications
4
15
1
2
Order By: Relevance
“…(38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) However, with the exception of vinculin (14,15) the genes reported to be associated with early recurrence of HCC in transcriptomic studies were not identified in this study, a fact possibly due to the current detection limitations of 2D-DIGE using the CyDye DIGE Fluor minimal dye. To improve the sensitivity of our proteomic studies, we are now considering the use of prefractionation methods, narrow range IPG gels, more sensitive fluorescent dye such as the CyDye DIGE Fluor saturation dye, and larger format 2D gels.…”
Section: Discussioncontrasting
confidence: 51%
“…(38,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49) However, with the exception of vinculin (14,15) the genes reported to be associated with early recurrence of HCC in transcriptomic studies were not identified in this study, a fact possibly due to the current detection limitations of 2D-DIGE using the CyDye DIGE Fluor minimal dye. To improve the sensitivity of our proteomic studies, we are now considering the use of prefractionation methods, narrow range IPG gels, more sensitive fluorescent dye such as the CyDye DIGE Fluor saturation dye, and larger format 2D gels.…”
Section: Discussioncontrasting
confidence: 51%
“…The extent of elevated gp96 expression in liver tissues was significantly correlated with the disease progression of HBV infection, but high level expression of gp96 did not induce an immunoresponse against HBV infection as expected [13]. Other studies involving gp96 as adjuvant have also indicated that highdose gp96 administration can down-regulate inflammatory events and anti-tumor effect [14,15].…”
mentioning
confidence: 75%
“…Interestingly, a similar GRP94 distribution pattern has been reported in other tumor cells. 42 Moreover, the increase in GRP94 level was shown to be correlated with the disease progression of HBV infection 66 although unrelated to HCV, HBV shows pathological progress similar to that of HCV. The levels of GRP94 were greatest in HCC patients and lowest in patients with chronic HBV infection, with intermediate levels reported in patients with cirrhosis.…”
Section: Discussionmentioning
confidence: 99%
“…40 Moreover, increased levels of GRP94 were observed when a chronic hepatitis B virus (HBV) infection progressed to cirrhosis and hepatocellular carcinoma (HCC). [41][42][43] Inhibitors of Hsp90 and GRP94 (such as geldanamycin and its less toxic derivative 17-AAG) have been investigated for efficacy in cancer treatment. Geldanamycin and 17-AAG inhibit Hsp90 and GRP94 by binding competitively to its N-terminal adenosine triphosphate-binding site.…”
mentioning
confidence: 99%